Handbook of carbohydrate engineering (Taylor & Francis, 2005)
The book oprsents the fundamental of carbohydrate engineering, addressing concepts in structure, biosynthesis, and biological functions for a variety of carbohydrates with a particular emphasis on mammalian glycoproteins, and their N-linked aligosaccharides, glycolipids, sialic acid, as well as polisaccharides from both eukaryotes and bacteria.